Behavioral Effects of a Potential Novel TAAR1 Antagonist - Lam, Vincent M.; Mielnik, Catharine A.; Baimel, Corey; Beerepoot, Pieter; Espinoza, Stefano; Sukhanov, Ilya; Horsfall, Wendy; Gainetdinov, Raul R.; Borgland, Stephanie L.; Ramsey, Amy J.; Salahpour, Ali (Frontiers in Pharmacology, 2018)
TAAR1 is a G-protein coupled receptor expressed in the monoaminergic regions of the brain, and represents a potential novel therapeutic target for the treatment of neurological disorders. While selective agonists for TAAR1 have been successfully identified, only one high affinity TAAR1 antagonist has been described thus far. We previously identified four potential low potency TAAR1 antagonists through an in silico screen on a TAAR1 homology model. One of the identified antagonists (compound 22) was predicted to have favourable physicochemical properties, which would allow the drug to cross the blood brain barrier. In vivo studies were therefore carried out and showed that compound 22 potentiates amphetamine- and cocaine-mediated locomotor activity, consistent with behaviours observed in TAAR1-KO animals. In order to assess whether the effects of compound 22 were mediated through TAAR1, experiments were carried out on TAAR1-KO mice. The results showed that compound 22 is able to enhance amphetamine- and cocaine-mediated locomotor activity, even in TAAR1-KO mice, suggesting that the in vivo effects of this compound are not mediated by TAAR1. In collaboration with Psychoactive Drug Screening Program, we attempted to determine the targets for compound 22. PDSP results suggested several potential targets for compound 22 including, the dopamine, norepinephrine and serotonin transporters; as well as sigma 1 and 2 receptors. Our follow-up studies using heterologous cell systems showed that the dopamine transporter is not a target of compound 22. Therefore, the biological target of compound 22 mediating its psychoactive effects still remains unknown.